Parenting Styles: The Key to Adaptation Self Efficacy of Ministry of Health Semarang Health Polytechnic - Nurisda Eva Irmawati; Oktovyanne Salsabilla (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Suicide among university students, particularly those who have moved away from home, is a serious issue. One contributing factor is their level of adaptation self-efficacy. Parenting styles are thought to influence this self-efficacy, though this link hasn't been firmly established in research. This study aimed to investigate this relationship among students at Semarang Health Polytechnic. Using a correlational approach with a cross-sectional method, 53 second-year students were surveyed from campus 1 of Semarang Health Polytechnic, chosen via total sampling. The data, analyzed using Spearman's Rank correlation test, revealed a significant connection (p = 0.000, correlation coefficient = 0.520) between parenting styles and adaptation self-efficacy among these students.Most respondents experienced democratic parenting (62.3%) and showed adequate adaptation self-efficacy (60.4%). This suggests that democratic parenting positively influences adaptation self-efficacy among students living away from home. In conclusion, this study confirms the link between parenting styles and adaptation self-efficacy among students at Semarang Health Polytechnic, emphasizing the role of supportive parenting in helping students adjust to new environments.